Carbon and water relations in perennial Kernza (Thinopyrum intermedium): An overview. (June 2020) - de Oliveira, Gabriel; Brunsell, Nathaniel A.; Crews, Timothy E.; DeHaan, Lee R.; Vico, Giulia
Highlights: Comprehensive review about the water and carbon cycles in perennial Kernza plants. Kernza has a relatively high water-use efficiency through the whole growing season. Kernza tends to have higher evapotranspiration rates when compared to annual counterparts. Kernza has shown to act as carbon sink on a long-term basis. Abstract: Perennial crops have been proposed as a more sustainable alternative to annual crops, because they have extended growing seasons, continuous ground cover, reduced nutrient leakage, and sequester more carbon in the soils than annual crops. One example is intermediate wheatgrass ( Thinopyrum intermedium ), a perennial crop that has been used as a cool-season forage throughout the USA and Canada and also across its native range in Eurasia. Since the 1980′s, intermediate wheatgrass has been under domestication to improve seed fertility and grain yield. Commercial products are being sold under the trade name Kernza, owned by The Land Institute, located in Salina, Kansas, USA. This review provides a comprehensive framework about the physical and biological aspects involving the water and carbon cycles in Kernza plants. The main aspects we highlight here are based on previous findings regarding Kernza: i) the ability of maintaining a relatively high water-use efficiency throughout the whole growing season, which is beneficial to mitigate water stress, representing an important physiological mean to acclimate under severe, unfavorable weather conditions, and ii) its higher evapotranspiration (ET) and net carbon uptake rates, particularly when compared to annual counterparts. Only a thorough multifaceted assessment of the repercussion for carbon and water fluxes of a shift from annual crops to Kernza will allow assessing the perspectives of such novel perennial crop to support food security and a number of ecosystem services, particularly under future climates.